1855. Risk factors for early mortality in patients with carbapenem-resistant Acinetobacter baumannii bacteremia. (15th December 2022) - Lee, Chan Mi; Kim, Chung-Jong; Kim, Seong Eun; Park, Kyung-Hwa; Bae, Ji Yun; Choi, Hee Jung; Jung, YoungHee; Lee, Seung Soon; Choe, Pyoeng Gyun; Park, Wan Beom; Suk Kim, Eu; Song, Je Eun; et al.
Abstract: Background: Although many deaths due to carbapenem-resistant Acinetobacter baumannii (CRAB) bacteremia occur within a few days after the onset of bacteremia, risk factors for early mortality (EM) have not been deeply investigated. We aimed to determine the risk factors for EM and the difference between risk factors associated with EM and late mortality (LM) in CRAB bacteremia. Methods: All patients with CRAB bacteremia in 10 hospitals during a 1-year study period were identified. We prospectively collected patients' clinical data, including microbiological and demographic data, underlying comorbidities, origin of bacteremia, severity of illness, antibiotic therapy, and mortality. Among the cases with mortality within 30 days, EM and LM were defined as death within 3 and more than 5 calendar days from the first positive blood culture, respectively. Results: A total of 212 CRAB bacteremia cases were included in the analysis. Of 122 (57.5%) patients with 30-day mortality, EM was observed in 75 (61.5%) patients and LM in 39 (32.0%) patients. The proportion of severe sepsis or septic shock, Pitt score, and Sequential Organ Failure Assessment (SOFA) score were significantly higher in 30-day deaths than 30-day survivors. These factors of clinical severity were also significantly higher in patients with EM than those with LM. While urinary tract infection as the factor of site of infection and the severity of illness were independent predictors of LM, only factors representing the severity of illness were independent risk factors for EM. Appropriate empirical antibiotic therapy was associated with reduced risk of EM. Conclusion: The difference between risk factors for EM and LM was identified in this study. Our data suggest that a large proportion of CRAB bacteremia with high severity progress to a rapidly fatal course, regardless of the underlying diseases or source of infection. Further studies might be needed to investigate the microbiological factors associated with CRAB and pathogen-host interaction in patients with EM. Disclosures: All Authors : No reported disclosures.